The Applications of Functional Variants of Jensen's Inequality - Zlatko Pavić (Journal of Function Spaces and Applications)
The paper is inspired by McShane's results on the functional form of Jensen's inequality for convex functions of several variables. The work is focused on applications and generalizations of this important result. At that, the generalizations of Jensen's inequality are obtained using the positive linear functionals.